Determinants of sustainable growth in Indian banking industry: an ISM approach. (18th July 2022) - Dogra, Nikhil; Adil, Mohd
The importance of sustainability for nation building has recently drawn considerable interest from researchers. It is highly acknowledged in the literature that the acceptance of sustainable policy is a tool for the inclusive progress and growth of the economy. Although, manufacturing industry has received considerable attention as compared to service industry, sustainability at banks is the newest approach. The purpose of this study is to the key determinants that affects bank's sustainability and then investigates the mutual relationships among these determinants. Interpretive structural modelling is employed to investigate the interrelationships among the key determinants. The results show that the environmental concern and social sustainability are one of the critical determinants related to sustainability at banks. The study findings have far reaching implications for bank management, scholars and other stakeholders.